Podział terytorialny państwa a struktury Kościoła katolickiego w Polsce - Mielczarek-Mikołajów, Justyna; Mikołajów, Konrad (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2017)
The article concerns the territorial units of the state (municipality, district, province) and the Church (parish, diocese, metropolis). Territorial structures of the Roman Catholic Church in Poland since the beginning underwent constant change and most of the time does not coincide with administrative boundaries. From a theoretical point of view, these units do not have to be identical. Note, however, that the state and the Church make up the same people operating within a social space, so important is the cooperation between the two institutions to ensure the common good and the citizen
Keywords: Kościół rzymskokatolicki; struktury terytorialne państwa; społeczeństwo obywatelskie